2009
DOI: 10.1111/j.1742-4658.2009.07316.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor and acceptor substrate selectivity among plant glycoside hydrolase family 32 enzymes

Abstract: Plant family 32 glycoside hydrolase enzymes include hydrolases (cell wall invertases, fructan exohydrolases, vacuolar invertases) and fructosyltransferases. These enzymes are very similar at the molecular and structural levels but are functionally different. Understanding the basis of the functional diversity in this family is a challenging task. By combining structural and site‐directed mutagenesis data, Asp239 in AtcwINV1 was identified as an amino acid critical for binding and stabilizing sucrose. Plant fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 37 publications
0
58
0
Order By: Relevance
“…The mutagenesis in search of the important residues responsible for substrate recognition and the type of catalytic reaction has been studied in plant GH32 members and GH68 microbial levansucrases (51)(52)(53)(54)(55)(56)(57)(58). The superimposed structures show that Glu-318 in AjFT is at a position equivalent to Asp-239 in AtcwINV, which has been shown to be critical for binding and stabilizing sucrose (Fig.…”
Section: Structural Comparison Of the Active-site Pocket Of Ajft Withmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutagenesis in search of the important residues responsible for substrate recognition and the type of catalytic reaction has been studied in plant GH32 members and GH68 microbial levansucrases (51)(52)(53)(54)(55)(56)(57)(58). The superimposed structures show that Glu-318 in AjFT is at a position equivalent to Asp-239 in AtcwINV, which has been shown to be critical for binding and stabilizing sucrose (Fig.…”
Section: Structural Comparison Of the Active-site Pocket Of Ajft Withmentioning
confidence: 99%
“…2) (55). The Asp/Arg(Lys) pair located at the loop connecting the second and third strands of blade IV (corresponding to Glu-318/His-332 in AjFT) and the hydrogen bond network created by this D/R pair were thus suggested for recognition of sucrose as a substrate (53)(54)(55). The equivalent residue at this position is Phe-233 in fructan 6-exohydrolase of the sugar beet Beta vulgaris.…”
Section: Structural Comparison Of the Active-site Pocket Of Ajft Withmentioning
confidence: 99%
“…Depending on the hydroxyl group of the acceptor molecule, which is subject to deprotonation by the acid-base catalyst, FOS with different types of ␤-fructosyl linkages will be obtained. Different fructosyl transferases have distinct donor and acceptor substrate specificities (34). GH-J enzymes share a ␤-propeller catalytic domain with three conserved acidic amino acids referred to as the "catalytic triad."…”
mentioning
confidence: 99%
“…Several studies in which specific residues have been mutated by site-directed mutagenesis have reported changes in the pattern of products recovered (2,20,27), although the conclusions of these studies still do not offer a complete picture of the transfructosylation mechanism. One of the questions that remains unanswered is which residues determine the formation of either ␤(2,1) or ␤(2,6) linkages (34).…”
mentioning
confidence: 99%
“…Fructosyltransferases operate via a retaining catalytic mechanism, with the Asp39, Asp164 and Glu216 residues acting as a nucleophile, transition-state stabilizer and general acid/base catalyst, respectively. These residues also play a critical role in the binding of the terminal substrate and the catalytic reaction [31,35]. Compared with the wild type enzyme, the N38L, S99A and Y282A mutant enzymes had lower K m and higher V max values, which indicated that they were exhibiting higher binding affinity towards the substrates than the wild type r-AoFT enzyme [36].…”
Section: Identification Of Crucial Amino Acid Residue For R-aoft Actimentioning
confidence: 99%